Freshwater - Emezi, Akwaeke (London, Faber & Faber, 2018)
A young Nigerian woman, Ada, who develops separate selves within her as a result of being born 'with one foot on the other side.' Ada begins her life in the south of Nigeria as a troubled baby and a source of deep concern to her family. Her parents, Saul and Saachi, successfully prayed her into existence, but as she grows into a volatile and splintered child, it becomes clear that something went terribly awry. When Ada comes of age and moves to America for college, the group of selves within her grows in power and agency. A traumatic assault leads to a crystallization of her alternate selves: Asghara and Saint Vincent. As Ada fades into the background of her own mind and these selves, now protective, now hedonistic, move into control, Ada's life spirals in a dark and dangerous direction.
Title from container.
Recordable compact discs.
Read by the author.
Keywords: Women -- Nigeria -- Fiction; Identity (Psychology) -- Fiction; Dissociative disorders -- Fiction